Navigating the Australian Social Media Ban: Reputation Risk and Defensive Marketing Strategies - Aldi Adi Pratama (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2025)
Purpose – This research aims to analyze the strategic responses of Major Technology Platforms (MTPs) to Australia's Social Media Minimum Age (SMMA) regulation, which prohibits access for children under the age of 16. The primary focus is to evaluate internal organizational culture shifts and the effectiveness of defensive global marketing strategies in mitigating reputational risks. Methodology – This research employs a qualitative phenomenological case study approach to analyze the strategic impact of ethics-based regulations. Thematic analysis is applied to understand how MTP leadership interprets regulatory pressures and integrates digital governance principles into corporate practices. Findings – This research finds that compliance with the social media Minimum Age regulation compels Major Technology Platforms to transform from a 'growth-first' to a 'safety-first' model, where children under 16 are no longer viewed as monetization assets but as vulnerable stakeholders. The analysis indicates that reputational risks are triggered by previous failures in age-limit enforcement, which now demand the integration of compliance functions from the early stages of product development (Safety by Design). Practical Implications – Major Technology Platforms must immediately diversify their business models by investing in alternative monetization strategies such as subscriptions, non-targeted e-commerce, or high-value content partnerships to reduce dependence on advertisements targeting adolescents. Companies need to position themselves as active contributors in co-regulation to formulate global safety standards. Social implications – This transformation strengthens global digital governance that prioritizes ethics and safety over short-term profits. By leveraging input from organizations such as the United Nations Children's Fund, the industry can steer policies away from simple total bans toward a fundamental improvement in platform quality through the strengthening of digital resilience.